Impactos da pandemia da covid-19 na cadeia produtiva do pescado na região Centro-Sul Mato-grossense, Brasil - Moraes, Clarissa Rocha (2020)
In December 2019, a new coronavirus was detected in Wuhan, Hubei province in China, as the causative agent of pneumonia, which spread from the local fish market. Designated as COVID19, on March 12, 2020 the disease was declared a pandemic, with more than 76 million confirmed cases worldwide. In Brazil, more than 7 million people were contaminated until the moment of elaboration of this work, the main measure to contain the spread of the disease, was social isolation, in which it was recommended to avoid places of agglomeration of people. Some states have declared a blockade of passage, with permission to exit only to carry out essential activities, because the main route of contagion of the disease is through the contact of healthy people with infected individuals. This whole condition has the potential to modify the normal dynamics of systems functioning, including essential ones, such as food systems. In 2017, fish accounted for 17% of all animal protein intake, with production of more than 172 million tons, representing an important activity worldwide, and the impacts of the pandemic on the fish chain have not yet been accurately reported, since the crisis is still ongoing. This work aimed to compile the information that has been generated, so far, in the literature, on the impact of the COVID-19 pandemic on the food production chain, as well as on the fish production chain in the central-south-matogrossense region, through application of questionnaires to the actors of the different links in this chain. The first perceptions were the increase in the price of inputs, but the demand for fish according to producers remained stable by 38.10% of respondents. The same occurred for the factories that produce fish feed (50%) and retailers (37.50%) that sell fish in the region, unlike the meatpackers that 100% of respondents declared to have decreased demand, and their productive capacity due to the pandemic. As for consumers, most declared that before the pandemic, consumption was carried out “2 to 3 times a month” (27.42%), however, with the advent of the pandemic, consumption began to be carried out “rarely” (31.33 %). The place of consumption was already carried out mostly at home (68.56%), however, with the advent of the pandemic, this value increased to 75.84% due to the indication of social isolation. More studies need to be carried out in other regions in order to have a clear view of the impacts of the pandemic on consumers and producers, processors and fish traders in the state of Mato Grosso.